Adaptive fault recovery strategy of LCC‐MMC based hybrid HVDC. Issue 16 (23rd April 2021) - Sayed Tassawar Hussain, Kazmi; Song, Guobing; Wang, Ting; Hou, Junjie; Masood, Bilal
Abstract: Hybrid HVDC consisting of line commutated converter (LCC) on rectifier side and modular multilevel converter (MMC) on inverter side is the favourable future trend of HVDC projects utilising the advantages of both converter technologies. However, fault clearing and adaptive restart capabilities of such hybrid HVDC are not much investigated in the literature. In this paper fault clearing of hybrid HVDC transmission line is investigated using mechanical DC breaker at MMC terminal and forced firing angle retardation at LCC terminal. Then, the characteristics of the line voltages are analysed during the fault blocking states of converters to clear the transient fault. Characteristics of the line voltages of LLC rectifier have shown prominent difference under permanent and temporary fault states, and also dependent on the severity of fault. Therefore, based on line voltage characteristics, a restart strategy is proposed for hybrid HVDC which is adaptive to the fault characteristics. Several PSCAD/EMTDC based simulation studies are conducted to validate the proposed fault recovery strategy. Simulation results validate the effectiveness of the proposed strategy for hybrid HVDC under DC line faults.